Focus on leadership. (Business strategy series, 2007)
This e-book contains a series of articles on leadership and the details the successes and failures of various leaders within high profile organizations. New theories are presented as well as examples from practice. Topics covered include ethics, women leaders, organizational culture and learning, and presentation skills. This e-book includes contributions from authors from Bain & Company, and the Institute of Applied Innovation Research.